Principles of the Form of the Welcome and Serasan Sekentenan Dance in Musi Rawas Regency - Lusiana Dewi; Desi Puspita Sari; Niken Clarisa (Yayasan Baru Haji Samsudin, 2024)
This study aims to describe the principles of the Sambut Lan Serasan Sekentenan Dance by using a choreographic approach according to Y. Sumandiyo Hadi's theory in the principles of dance form, in one of the courses in semester 6 (six) in the Performing Arts Education Study Program, Faculty of Teaching and PGRI Palembang University of Education. What will be discussed is the principle of the form of motion in Sesentenan's Sambut Lan Serasan Dance, which includes wholeness, variation, repetition, transition, series, comparison, and climax. The Serasan Sekentenan Sambut Lan Dance is a development of the Musi Rawas Welcome Silampari Dance. The word Lan Serasan Sekentenan means a peaceful earth, mutual cooperation, tolerance and hand in hand. The Sambut Lan for special guests. Where the Sambut Lan Serasan Sekentenan Dance uses a tepak property Serasan Sekentenan dance is included in the type of traditional dance as a welcoming dance containing a betel leaf as a symbol of respect for certain guests. This welcoming dance is performed by 8 dancers, consisting of 5 female dancers and 3 male dancers. The make-up in this dance uses corrective make-up. Clothing in this dance uses a bracketed shirt. The use of identical colors, namely red in the sambut lan serasan sekentenan dance.